Steep discounting of delayed monetary and food rewards in obesity: a meta-analysis. Issue 11 (15th June 2016) - Amlung, M.; Petker, T.; Jackson, J.; Balodis, I.; MacKillop, J.
Abstract : Background: An increasing number of studies have investigated delay discounting (DD) in relation to obesity, but with mixed findings. This meta-analysis synthesized the literature on the relationship between monetary and food DD and obesity, with three objectives: (1) to characterize the relationship between DD and obesity in both case–control comparisons and continuous designs; (2) to examine potential moderators, including case–control v. continuous design, money v. food rewards, sample sex distribution, and sample age (<18 v. >18 years); and (3) to evaluate publication bias. Method: From 134 candidate articles, 39 independent investigations yielded 29 case–control and 30 continuous comparisons (total n = 10 278). Random-effects meta-analysis was conducted using Cohen's d as the effect size. Publication bias was evaluated using fail-safe N, Begg–Mazumdar and Egger tests, meta-regression of publication year and effect size, and imputation of missing studies. Results: The primary analysis revealed a medium effect size across studies that was highly statistically significant ( d = 0.43, p < 10 −14 ). None of the moderators examined yielded statistically significant differences, although notably larger effect sizes were found for studies with case–control designs, food rewards and child/adolescent samples. Limited evidence of publication bias was present, although the Begg–Mazumdar test and meta-regression suggested a slightly diminishing effect size over time. Conclusions: Steep DD of food and money appears to be a robust feature of obesity that is relatively consistent across the DD assessment methodologies and study designs examined. These findings are discussed in the context of research on DD in drug addiction, the neural bases of DD in obesity, and potential clinical applications.